NEPOTISME DALAM PANDANGAN HADIST - Alang, Agung Zulkarnain; Zulfahmi,; Sakka, Abdul Rahman (Jurnal Dakwah Tabligh, 2024)
The purpose of this study is to explore hadiths that explain nepotism. This research is Library Research. The data sources used come from several literature and library materials related to the topic discussed. The study results show that the Hadith about nepotism narrated by Imam Ahmad bin Hanbal is of valid quality. This conclusion is based on the fact that the narrations of the hadith, as assessed by the critics, have the status of tsiqah. In addition, the hadith in question does not contradict the content of the Qur'an, namely that those who disobey Allah and His Messenger will be put in hell. The practice of nepotism that is prohibited by Islamic teachings is solely based on family or relatives’ considerations without paying attention to the ability and professionalism as well as the nature of trust of a person who will be given a position. As for nepotism it is accompanied by consideration of ability and professionalism as well as the nature of trust of a person who will be given a position, it is not prohibited.